JURIDICAL REVIEW OF ONLINE GAMBLING CRIME IN NORTH SUMATERA - Yasmirah Mandasari Saragih; Ferry Irmawan; Sony Prayudha Winata; Riki Hamdany (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Law enforcement is carried out by law enforcers. In addition to depending on the legal awareness of the community, the implementation of law in society is also very much determined by law enforcement officials. Law enforcement by the National Police against perpetrators of online gambling crimes at the North Sumatra Regional Police is carried out based on the provisions of Law No. 19 of 2016 on amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions. Law enforcement against perpetrators of online gambling crimes in the police. The increasing mode of online gambling crime is not accompanied by an increase in the quality and quantity of Polri personnel. Lack of mastery of information technology by investigators in uncovering perpetrators of online gambling crimes. Lack of identity of the perpetrators and lack of witnesses. Lack of evidence in the filing process. The lack of cooperation that exists between the Police and providers and the public to obtain information related to online gambling crimes. The lack of cooperation that exists between the Police and the Public Prosecutor in the process of investigating criminal acts of online gambling. This research has a formulation of the problem of how the efforts of the North Sumatra Regional Police in eradicating online gambling crimes in North Sumatra and how legal sanctions for perpetrators of online gambling crimes also have normative and juridical research methods that are linked to laws and all opinions of legal experts. The lack of cooperation that exists between the Police and the Public Prosecutor in the process of investigating criminal acts of online gambling. This research has a formulation of the problem of how the efforts of the North Sumatra Regional Police in eradicating online gambling crimes in North Sumatra and how legal sanctions for perpetrators of online gambling crimes also have normative and juridical research methods that are linked to laws and all opinions of legal experts. The lack of cooperation that exists between the Police and the Public Prosecutor in the process of investigating criminal acts of online gambling. This research has a formulation of the problem of how the efforts of the North Sumatra Regional Police in eradicating online gambling crimes in North Sumatra and how legal sanctions for perpetrators of online gambling crimes also have normative and juridical research methods that are linked to laws and all opinions of legal experts.